Software/hardware system for automatic monitoring of rectification - Dubrovskii, I. I.; Luk’yanov, V. L.; Dubrovskii, V. I. (Measurement techniques, 2007)
Creation of software is considered for visual monitoring of changes in temperature profile with the aim of studying the efficiency of rectification. The dynamics of the temperature profile over the height of a rectification column are displayed on a monitor screen on a real time scale.[PUBLICATION ABSTRACT]